2022
DOI: 10.1111/apt.16779
|View full text |Cite
|
Sign up to set email alerts
|

Association between ultrasound quality and test performance for HCC surveillance in patients with cirrhosis: a retrospective cohort study

Abstract: Background: Ultrasound visualisation is limited in approximately 20% of patients with cirrhosis undergoing hepatocellular carcinoma (HCC) surveillance; however, it is unknown if impaired visualisation directly impacts test performance. We aimed to evaluate the association between ultrasound visualisation and surveillance test performance. Methods:We performed a retrospective cohort study among patients with cirrhosis, with or without HCC, who underwent ultrasound-based surveillance at two large health systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…This gap is not surprising given ultrasound in the United States is conducted by technicians with frozen images subsequently interpreted by radiologists, whereas ultrasound is typically conducted and interpreted concurrently by clinicians in Europe and Asia. [ 29 ] Therefore, the need for alternative strategies, such as biomarkers, may vary by site and be driven by local performance of ultrasound‐based surveillance rather than pooled global estimates. Further, issues with ultrasound‐based surveillance will likely become more prevalent as cirrhosis etiologies shift from being viral hepatitis predominant to an increasing proportion related to alcohol and nonalcoholic steatohepatitis‐related cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…This gap is not surprising given ultrasound in the United States is conducted by technicians with frozen images subsequently interpreted by radiologists, whereas ultrasound is typically conducted and interpreted concurrently by clinicians in Europe and Asia. [ 29 ] Therefore, the need for alternative strategies, such as biomarkers, may vary by site and be driven by local performance of ultrasound‐based surveillance rather than pooled global estimates. Further, issues with ultrasound‐based surveillance will likely become more prevalent as cirrhosis etiologies shift from being viral hepatitis predominant to an increasing proportion related to alcohol and nonalcoholic steatohepatitis‐related cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was in line with a finding from a previous research reporting that inadequate US training programs were a potential barrier to proper usage of US for HCC surveillance in developing countries. [16] Additionally, we found that the AFP test was unavailable in 72.4% of community hospitals. This high unavailability rate might be due to the outweighed benefits and versatility of the US machine compared to the AFP test.…”
Section: Discussionmentioning
confidence: 99%
“…Its poor prognosis is partly driven by frequent late‐stage detection due to suboptimal sensitivity of current surveillance tests—abdominal ultrasound and alpha fetoprotein—which miss over one‐third of HCC cases at an early stage 1 . Ultrasound‐based surveillance is particularly subject to failure in obese patients and those with non‐viral etiologies of liver disease, highlighting a clear need for alternative strategies 2 …”
Section: Introductionmentioning
confidence: 99%